Clinical Utilization of Pharmacogenetics in Psychiatry – Perspectives of Pharmacists, Genetic Counselors, Implementation Science, Clinicians, and Industry - Brown, Lisa; Eum, Seenae; Haga, Susanne B.; Strawn, Jeffrey R.; Zierhut, Heather (Pharmacopsychiatry, 2019)
Introduction The use of pharmacogenomic (PGx) testing to guide decisions and improve patient outcomes has increased in recent years. PGx testing represents a decision support tool that may inform dosing, increase the likelihood of treatment response, and identify patients at risk for medication side effects.Methods This is a narrative review of utilization of PGx testing in psychiatry from stakeholders including, pharmacists, genetic counselors, implementation scientists, industry, and clinicians.Results While many limitations exist to streamline use of PGx testing in psychiatry, various stakeholders are crucial to clinical implementation.Discussion PGx testing can assist in medication selection and improve patient outcomes; however, more data are needed to understand when and how to incorporate PGx testing into psychiatric practice.
Keywords: pharmacogenomics; pharmacogenetics; implementation